HUBUNGAN ANTARA INTERAKSI SOSIAL SISWA DENGAN PRESTASI BELAJAR BAHASA INDONESIA SISWA MADRASAH IBTIDAIYAH SE-KABUPATEN GORONTALO - Andi Nurwati (Jurnal Cakrawala Pendidikan, 2009)
This study aimed to investigate the relationship between students’ social interactions and their Indonesian language learning achievement in Madrasah  Ibtidaiyahs in Gorontalo Regency. Students’ social interactions included parents’ upbringing patterns, the peer interaction, and the teacher-student interaction in the learning process. This study was an ex post facto study involving parents’ upbringing patterns, the peer interaction, and the teacher-student interaction as the independent variables X1, X2, and X3, respectively. The intervening variable was the learning motivation (X4) and the dependent variable (Y) was the Indonesian language learning achievement. The research population comprised all Year V students in 25 Madrasah Ibtidaiyahs in Gorontalo Regency. The sample was selected by using the multi-stage sampling technique and it consisted of 9 Madrasah Ibtidaiyahs involving 101 Year V students. The research instruments included a questionnaire to measure the independent and intervening variables. The data were analyzed using the multiple regression and path analyses at p 0.05. The results of the research data analysis showed that the direct and indirect effects of the parents’ upbringing patterns (X1) on the learning achievement through the learning motivation (X4) were 0.177 and 0.0458. The direct and indirect effects of the peer interaction (X2) on the learning achievement through the learning motivation (X4) were 0.277 and 0.0717. The direct and indirect effects of the teacher-student interaction (X3) on the learning achievement through the learning motivation (X4) were 0.266 and 0.0689. The direct and indirect effects of all independent variables as an aggregate on the learning achievement through the learning motivation were 0.678 and 0.1756. The peer interaction was the one with the strongest direct effect, namely 0.277, on the Indonesian language learning achievement among other variables in the study.Keywords: social interaction, parents’ upbringing patterns, peer interaction, teacher-student interaction, learning achievement